The Impact of First Aid Training on Knowledge and Practical Skills Among Sports Vocational Students - Alfi Ari Fakhrur Rizal; Agung Sugiarto; Ayuthya Safitri Nuraz’mi; Nuraini Sri Agustina; Ririn Aliya Putri; Nina Maulida; Tassya Indri Fadillah (Ahmar Metastasis Health Journal, 2026)
Musculoskeletal injuries represent a significant challenge in youth athletics, necessitating effective immediate management to prevent complications. This study aimed to evaluate the effectiveness of a targeted musculoskeletal injury first aid training program on the knowledge and practical skills of Grade 10 student-athletes at the Indonesian Special Sports School (SKOI), East Kalimantan. Utilizing a pre-experimental, one-group pretest-posttest design, 30 student-athletes participated in a structured intervention covering dislocations, sprains and strains, fractures, bleeding, and muscle cramps. The findings revealed statistically significant improvements across all injury categories (p<0.001), with substantially large effect sizes indicating the program's strong efficacy. Notably, the sprain and strain category showed the most pronounced advancement, with practical skills rising from a low baseline to high proficiency (Cohen's d=7.06). Furthermore, robust practical skill acquisitions were consistently documented for fractures (d=3.66), bleeding (d=3.09), muscle cramps (d=2.63), and dislocations (d=2.49). These results demonstrate that the training successfully bridged the gap between theoretical comprehension and on-field application. In conclusion, structured first aid education significantly enhances student-athlete competence, supporting its integration as a sustainable core component of sports school curricula to mitigate injury-related risks.